FOOD-RELATED TELEVISION ADVERTISEMENTS FROM THE PERSPECTIVE OF CHILDREN - Bianka Barta; Robert Sandor Szucs (European Scientific Journal, ESJ, 2015)
During our research, we examined how often do children and teenagers sit down in front of television screens and thus come into contact with television advertisements and the sales promotion tools often used by corporations. We mostly placed emphasis on brand-related cartoon characters used by corporations. In the case of children, we can say that an appropriately made combination of a well-placed cartoon character, logo and colors has a notable influence. Not only they recognize brands easier with the help of these, they also trigger emotional attachment. All of these contribute to the development of brand loyalty, which if develops during childhood, can last an entire lifetime.